HEYDAR ALIYEV AS A FOUNDER OF NATIONAL MULTICULTURALISM AT THE STATE LEVEL - Abilova, Zulfiyya (International Journal of Innovative Technologies in Social Science, 2020)
The presented scientific article states that one of the main tasks of states is achieving tolerance in human relations and creating favorable conditions for people of different religions and cultures to live in peaceful environment. Azerbaijan has historically been a space where representatives of different ethnic groups and religions lived in an atmosphere of peace and friendship. Heydar Aliyev chose the exact ideological goal of the future successful development of Azerbaijan and, with his far-sighted and wise policy, developed the tradition of multiculturalism that had formed over the centuries and raised it to a qualitatively new stage.